INTERNATIONAL COOPERATION IN UZBEK CLASSICAL MUSIC IN RECENT YEARS - Murodova Sadoqat Qoziboyevna (Web of Journals Publishing, 2024)
In this article, information about the genres inherited from Uzbek music, their types is presented. Folk and professional genres in Uzbek music are interpreted.
Keywords: folklore, music, genre, people, creativity, art, tradition, instrumental.